Educating managers as a key factor in effective management of healthcare units - Furtak, Marzena; Książek, Piotr; Rzemek, Cezary; Zdrojkowski, Jarosław (Polish Journal of Public Health, 2010)
Decentralization in the healthcare sector today require handing over the competence to lower rank managers; in particular to managers of public healthcare units and therefore they need to gain more qualifications so as to be able to take expert decisions and achieve more effective results in their job. Obvious demand for highly qualified managers in the healthcare sector results from the changes in the functioning of this sector. With with considerably diminishing financial outlays, managers are expected not only to be more effective in their management of healthcare units, but also to minimize the expenditure costs. The abovementioned arguments lead to a general conclusion that only managers in the healthcare system with suitable qualifications and sufficient knowledge concerning finance, economics, law, management and administration are capable of meeting the requirements of rapid changes in this sector.